The antibacterial effect and physical performance of pit and fissure sealants based on an antibacterial core–shell nanocomposite. (May 2021) - Hu, Y.T.; Yu, F.; Tang, X.Y.; Wu, W.Z.; Zhang, P.; Hu, Z.H.; Chen, J.H.; Xing, X.D.; Xiao, Y.H.
Abstract: The application of pit and fissure sealants is a well-established method to prevent and treat early childhood caries. Resin-based sealants with antibacterial properties provide additional benefits for caries prevention in a cariogenic oral environment. The objective of this study was to evaluate the effect of an antibacterial core–shell AgBr/cationic polymer nanocomposite (AgBr/BHPVP) on the properties of a resin-based pit and fissure sealant. A commercialized pit and fissure sealant without fluoride, Concise (3M, ESPE, USA), was used as the parent material and negative control. Experimental antibacterial sealants were formulated by the addition of AgBr/BHPVP nanoparticles at mass fractions of 0.5, 1.0, and 1.5 wt% to the parent material. A fluoride-releasing sealant, Clinpro (3M, ESPE), was used as the positive control. Bacterial colony-forming unit (CFU) counts, metabolic activity tests, field emission–scanning electron microscopy (FE–SEM), and confocal laser scanning microscopy (CLSM) observations were used to evaluate the antibacterial properties of AgBr/BHPVP-modified sealants against Streptococcus mutans before and after five months of aging. The Vickers microhardness, degree of conversion, and microleakage level of the sealants were also investigated. According to the results of CFU counts and metabolic tests, sealants containing AgBr/BHPVP showed better contact-killing bactericidal activity against S. mutans than the two commercial sealants, irrespective of aging conditions (both P < 0.05). The AgBr/BHPVP-modified sealants also showed a significant inhibitory effect on the planktonic S. mutans around the cured sealant surfaces. In addition, the Vickers microhardness, degree of conversion, and microleakage level of the parent material were not damaged by modification with AgBr/BHPVP (P > 0.05). AgBr/BHPVP-modified pit and fissure sealant with a dual bactericidal mechanism is a promising option for the prevention of pit and fissure caries. Graphical abstract: Image 1 Highlights: A core-shell AgBr/cationic polymer nanocomposite (AgBr/BHPVP) exhibiting increased antibacterial activity. The AgBr/BHPVP-modified pit and fissure sealant inhibited Streptococcus mutans biofilm formation. The AgBr/BHPVP-modified sealants showed inhibitory effect on the planktonic S. mutans around the cured sealant surfaces. AgBr/BHPVP modified sealants with dual bactericidal mechanism will promisingly prevent occlusal caries.